Magnesium Sulfate Combined with Nifedipine Is Effective in Pregnancy-Induced Hypertension and Reduces Levels of Serum β2- Microglobulin and Retinol Binding Protein 4 - Jie SONG; Ruihong LAN; Humin GONG; Linmei ZHENG; Yang YANG; Dahua YI; Enze HU (Tehran University of Medical Sciences, 2019)
Abstracts Abstracts Abstracts